Tranexamic acid has no effect on postoperative pain control after arthroscopic rotator cuff repair: A prospective, double-blind, randomized controlled trial - Ryosuke Takahashi; Yukihiro Kajita; Yusuke Iwahori; Yohei Harada (Elsevier, 2023)
Background: The purpose of this study was to compare the efficacies of tranexamic acid (TXA) versus placebo after arthroscopic rotator cuff repair (ARCR). Methods: This prospective, double-blind, and randomized study was conducted in 70 patients who underwent ARCR from 2021 to 2022 at our hospital. Thirty-four shoulders were randomly assigned to the TXA group, and 36 to the control group; TXA (10 mL) and normal saline (10 mL) were administered locally after surgery and in the control group, respectively. We evaluated visual analog scale pain scores at rest, during activity, and at night and the circumference and diameter of the shoulder joint in both groups preoperatively and at 1, 2, and 3 days, and 1 week after the surgery. We compared and analyzed the results between the groups. Statistical significance was set at a p-value of <0.05. Results: There was no significant difference in the visual analog scale scores at rest, during activity, and at night between the groups (p > 0.05). The circumference and diameter of the shoulder joint were not also significantly different between both groups (p > 0.05). Conclusion: Local TXA administration in patients who undergo ARCR does not significantly impact postoperative pain levels and the circumference and diameter of the shoulder joint.